1992
DOI: 10.1172/jci115672
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation-related expression of p19/nm23 nucleoside diphosphate kinase.

Abstract: High level expression of the nm23-Hl gene, which encodes for a nucleoside diphosphate kinase, has been found to correlate with diminished metastasis in some tumors but not in others. We have previously identified the protein product of the nm23-H1 gene in two-dimensional electrophoretic gels and have designated it p19/nm23. In neuroblastoma, higher levels of p19/ nm23, which are associated with amplification of the N-myc oncogene, large tumor mass, and metastasis, were observed in advanced stage tumors compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(69 citation statements)
references
References 25 publications
3
64
1
1
Order By: Relevance
“…It is likely that in certain tumours such as neuroblastoma (Hailat et al, 1991), colon cancer (Haut et al, 1991) and thyroid tumour (this study), Nm23 expression reflects cell proliferation. This conclusion is supported by recent study showing Nm23-Hl expression is related to cell proliferation (Keim et al, 1992) and our unpublished observation that Nm23 was expressed at higher levels in the early stage as compared to the late stage of mouse embryogenesis.…”
Section: Discussionsupporting
confidence: 88%
“…It is likely that in certain tumours such as neuroblastoma (Hailat et al, 1991), colon cancer (Haut et al, 1991) and thyroid tumour (this study), Nm23 expression reflects cell proliferation. This conclusion is supported by recent study showing Nm23-Hl expression is related to cell proliferation (Keim et al, 1992) and our unpublished observation that Nm23 was expressed at higher levels in the early stage as compared to the late stage of mouse embryogenesis.…”
Section: Discussionsupporting
confidence: 88%
“…The enhanced expression of NM23 in response to the epithelial mitogens KGF and EGF and its expression in hyperproliferative epidermis is in agreement with previous reports that link NM23-H1 expression to cell proliferative activity (Keim et al, 1992;Igawa et al, 1994). Interestingly, downregulation of the expression of NM23 proteins in a rat osteosarcoma-derived cell line (UMR-106) by an antisense approach revealed that the H1 isoform is more involved in the proliferative activity than the H2 isoform (Kimura et al, 2000), a result, which is consistent with the stronger induction of this NM23 subunit by KGF and EGF and its higher expression in psoriatic skin (this study).…”
Section: Discussionsupporting
confidence: 92%
“…NDPKs were originally identified as essential housekeeping enzymes required for the synthesis of nucleoside triphosphates by catalyzing the transfer of the ␥-phosphoryl groups from nucleoside triphosphates to nucleoside diphosphates via a phosphohistidine 118 enzyme intermediate, and they play a role in maintaining intracellular nucleotide concentrations (10). Altered expression of NDPK is also reportedly involved in many cellular processes, including oncogenesis (11,12), cellular proliferation (13), differentiation (14,15), motility (16), development (17), DNA repair (18), and apoptosis (19). In Escherichia coli, NDPK functions as a mutator gene and is not essential for viability (20).…”
mentioning
confidence: 99%